Central European Symposium on Thermophysics 2020 (Cest 2020) 2020
DOI: 10.1063/5.0025709
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a wall structure thermal transmittance sensitivity in function of meteorological parameters at constant internal surface temperature

Abstract: The paper presents 231 thermal transmittance values of a wall structure in function of different meteorological parameters while the indoor surface temperature was kept constant. In the calculations a 2D wall of a nearly zero energy building was examined at the external air temperature, wind speed and solar radiation, in accordance with the Hungarian Decree on the Determination of the Energy Characteristics of Buildings, ISO 6946:2017 and with typical meteorological year dataset. Results were calculated with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Previous research has shown that regulatory policies are the most effective means of reducing energy consumption in residential heating, highlighting the need for increased attention to this area for successful energy reduction [10]. Accurate estimates of the energy demands of buildings are required, taking into account the precise values of various factors [11,12]. The energy consumption of buildings is highly dependent on local meteorological conditions [13], regardless of the energy efficiency of individual buildings [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that regulatory policies are the most effective means of reducing energy consumption in residential heating, highlighting the need for increased attention to this area for successful energy reduction [10]. Accurate estimates of the energy demands of buildings are required, taking into account the precise values of various factors [11,12]. The energy consumption of buildings is highly dependent on local meteorological conditions [13], regardless of the energy efficiency of individual buildings [14].…”
Section: Introductionmentioning
confidence: 99%
“…A közél nülla énérgiaigényű épüléték énérgétikai kövétélményéit térmészétésén csak mégfélélő vastagságú hőszigétélő rétégékkél érhétjük él. Az alkalmazótt hőszigétélő rétégék vastagsága függ az anyag hőfizikai paramétéréitől és azók váltózásától, [16][17][18][19][20][21]. Középéürópai órszágókban, figyélémbé vévé az éghajlati viszónyókat és az élmúlt évtizédékbén alkalmazótt építési téchnólógiákat, égy átlagós hőtéchnikai paramétérékkél réndélkéző lakóépülétékbén a félhasznált énérgiaménnyiség közél 70%-át fűtésré fórdítják, [22].…”
unclassified